Implicit Attitudes and Smoking Behavior in a Smoking Cessation Induction Trial. Issue 1 (27th September 2016) - Lee, Hyoung S; Addicott, Merideth; Martin, Laura E; Harris, Kari J; Goggin, Kathy; Richter, Kimber P; Patten, Christi A; McClernon, F Joseph; Fleming, Kandace; Catley, Delwyn
Abstract: Introduction: Although studies have suggested that implicit attitudes may predict smoking-related decisions, evidence that changes in implicit attitudes toward smoking are related to changes in smoking behavior is lacking. Using data from a trial comparing interventions to induce quit attempts among unmotivated smokers, this study examined whether changes in implicit attitudes were associated with quit attempts and cessation after controlling for explicit motivation. Methods: Daily smokers recruited from the community completed measures of implicit attitudes (Implicit Association Test) and explicit measure of motivation to smoke at baseline, mid-intervention (week 12 [W12]) and follow-up (week 26 [W26]). Quit attempts and cessation were assessed at follow-up, and cessation was biochemically verified. Results: As hypothesized, Implicit Association Test scores became more negative from baseline to W12, a change that was sustained at follow-up. Logistic regression analyses in which implicit attitudes were used to predict smoking outcomes revealed that negative changes in implicit attitudes from baseline to W12 and from baseline to W26 were significantly related to quit attempts ( OR = 0.71, 95% CI [0.52, 0.97], p < .05 for both) independent of explicit motivation. Negative changes in implicit attitudes from baseline to W26 were significantly related to cessation ( OR = 0.50, 95% CI [0.25, 1.00], p < .05). Conclusions: Negative changes in implicit attitudes were associated with positive changes in smoking behavior independent of explicit motivation. This result indicates that smoking cessation interventions may be enhanced by incorporating strategies to change implicit attitudes, and that changes in implicit attitudes are also potentially important intervention outcomes. Implications: Smoking cessation interventions may be improved by going beyond the current focus on explicit psychological constructs and targeting automatic cognitive processes such as implicit attitudes. The results are encouragement to examine how best to manipulate smokers' implicit attitudes as well as to determine the effect on their smoking behavior.